"My voice speaks for itself": The experiences of three transgender students in American secondary school choral programs. (February 2020) - Palkki, Joshua
With the purpose of furthering lesbian, gay, bisexual, transgender, queer, questioning, and allies/agender/asexual (LGBTQA) dialogue in music education and to improve choral instruction for trans(gender) students, this multiple narrative case study explores the experiences of trans students in secondary school choral music programs in the United States. The emergent research design employed narrative and ethnographic techniques to honor and highlight voices of the three participants. The connection or lack thereof between voice and gender identity was different for each student. The policies of the students' school districts, school officials, choral programs, and state music organizations shaped and influenced the participants as they navigated their trans identity within the high school choral context. Mentors (including teachers) and other "important others" helped these students as they traversed their gender journeys. From this research, it emerges that schools and choral programs can make policy changes to better serve trans youth, and more professional development and incorporation of (trans)gender issues is necessary for choral music educators.